Enriched environment rescues bisphenol A induced anxiety-like behavior and cognitive impairment by modulating synaptic plasticity - Jiong Li; Guangyin Yu; Laijian Wang; Wenjun Zhang; Wenya Ke; Yifei Li; Danlei Liu; Keman Xie; Yuanyuan Xu; Caihui Cha; Guoqing Guo; Jifeng Zhang (Ecotoxicology and Environmental Safety)
Bisphenol A (BPA) is an exogenous endocrine disruptor in the environmental context, garnering attention for its harmful effects on the nervous system function and behavior. Research indicates that being exposed to BPA may result in anxiety-like behavior and impairment in cognitive function. Enriched environment (EE) is beneficial to improve cognitive behavior, but whether EE can improve BPA-induced behavioral impairment is still unclear. This research explored the possible pathways through which EE alleviates anxiety-like behavior and cognitive impairment in mice exposed to BPA. Except for the control mice, all mice received BPA treatment. After BPA treatment, some mice were housed normally, some housed with EE, and some were given NMDA and AMPA receptor agonists. Our research revealed that exposure to BPA results in anxiety-like behavior in open field and elevated-plus maze experiments. Additionally, spatial and learning memory cognitive impairments were observed in Y-maze and water maze tests. Furthermore, exposure to BPA led to a decrease in both the density and maturity of dendritic spines, as well as a reduction in neurite length and branch numbers. PSD-95, GluA1, and NR2A expression were down-regulated, and excitatory synaptic transmission was decreased. However, EE treatment increased dendrite spine density and maturity, up-regulated PSD-95, GluA1and NR2A expression, enhanced excitatory synaptic transmission, and relieved anxiety-like behavior and cognitive impairment in BPA mice. Furthermore, administering NMDA or AMPA receptor agonists to BPA mice led to an increase in dendritic spine density and maturity, a rise in mEPSC amplitude, as well as a restoration of anxiety-like behavior and cognitive deficits induced by BPA. The findings of this study provide proof that EE has a neuroprotective effect in reducing anxiety-related behavior and cognitive decline caused by BPA.